Effect of dry-wet cycles on the strength and deformation of the red-bed rockfill material in western Yunnan - Du, Jun; Shen, Xinggang; Li, Chenchen; Zhu, Weiwei; Feng, Guojian (Frontiers in Earth Science, 2023)
The shear strength deterioration of red-bed rockfill under the dry-wet cycle is the key factor affecting the slope stability of accumulation body. Studying the strength deterioration law and deterioration mechanism of red-bed rockfill can provide theoretical support for slope stability control. Through the disintegration resistance test of argillaceous siltstone rockfill in Lanping lead-zinc Mine, the disintegration characteristics of red-bed soft rock were studied. The effects of the number of dry-wet cycles on the cohesion, internal friction angle, shear dilation rate and shear modulus of the red-bed rockfill were investigated by using a dry-wet cycle shear tester to conduct shear tests on the reduced scale graded soil material, and the strength deterioration mechanism of the soils was revealed from the perspective of meso-structure. The results showed that argillaceous siltstone was rich in clay minerals and produces strong disintegration when exposed to water. The disintegration process could be divided into three stages: massive disintegration stage, transitional stage and stabilization stage. With the accumulation of dry-wet cycles, the shear dilation rate and shear modulus of the argillaceous siltstone rockfill gradually decrease, and the shear failure developed gradually from strain hardening to shear plastic flow, and the characteristic of weak stress softening occurred. After eight dry-wet cycles, the cohesion and internal friction angle of argillaceous siltstone rockfill materials decreased by 89.87% and 18.94%, respectively, indicating a higher effect on the cohesion than on the internal friction angle. The thickening of the bound water between the fine particles on the shear surface, the weakening of the coarse particle attachment, and the increase in the number of directionally arranged fine particles were the main reasons for the continuous deterioration of the soil strength.